1995
DOI: 10.1002/aic.690410617
|View full text |Cite
|
Sign up to set email alerts
|

Circulating fluidized bed as a catalytic reactor: Experimental study

Abstract: In recent years, the circulating fluidized bed as a reactor has experienced increasing application in industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 14 publications
6
55
0
Order By: Relevance
“…One reason is the expectation that the heat/mass transfer rate is high in a CFB and therefore of minor effects to the overall reaction rate. For example, the reaction coefficient k r of ozone decomposition over FCC particles was reported of the order of magnitude of 10 s À1 , while that of the overall mass transfer coefficient k p a p was 10 5 s À1 (Ouyang et al, 1995;Dong et al, 2008a). That means, the overall performance is controlled by reaction rate and the mass transfer is negligible (Damköhler number Da ¼ k r =k p a p ( 1) in the case that the flow is regarded homogeneous.…”
Section: Unclear Multiscale Structure: Obstacle To Cfb Applicationsmentioning
confidence: 93%
See 1 more Smart Citation
“…One reason is the expectation that the heat/mass transfer rate is high in a CFB and therefore of minor effects to the overall reaction rate. For example, the reaction coefficient k r of ozone decomposition over FCC particles was reported of the order of magnitude of 10 s À1 , while that of the overall mass transfer coefficient k p a p was 10 5 s À1 (Ouyang et al, 1995;Dong et al, 2008a). That means, the overall performance is controlled by reaction rate and the mass transfer is negligible (Damköhler number Da ¼ k r =k p a p ( 1) in the case that the flow is regarded homogeneous.…”
Section: Unclear Multiscale Structure: Obstacle To Cfb Applicationsmentioning
confidence: 93%
“…Fig. 8 shows typical results through simulating an ozone decomposition experiment (Ouyang et al, 1995). It is demonstrated that the conventional approach without considering the structural effects gives poor results in that the relevant mass transfer rate and ozone decomposition rate are overestimated significantly (Fig.…”
Section: Multiscale Modeling Of Mass/heat Transfermentioning
confidence: 97%
“…The overall conversion of O 3 inside the dense and the dilute phases is dominated by its intrinsic reaction rate, since k r ∼ (1.10) s −1 (Bi et al, 1992;Fryer et al, 1958;Ouyang et al, 1993Ouyang et al, , 1995Van Swaaij and Zuidenveg, 1972) while its mass transfer counterpart (k c p or k f p ) is of the order of magnitude of 10 5 s −1 . The meso-scale transfer is reserved for later comparison, thus the conversion rate of ozone in the dense and dilute phase can be written as follows:…”
Section: A Test Case Of Ozone Decompositionmentioning
confidence: 97%
“…The competition between mass transfer and reaction process makes the superficial reaction rate different from the intrinsic one (Levenspiel, 1999). To test the combined effects of mass transfer and reactions in a riser flow, we take the case of ozone decomposition performed by Ouyang et al (1995) (air-FCC particles, p = 1380 kg/m 3 , d p = 65 m, U g = 3.8.3.9 m/s, G s = 34.106 kg/m 2 s). The FCC catalyst particles used in that experiment fall into Geldart A in classification.…”
Section: A Test Case Of Ozone Decompositionmentioning
confidence: 99%
“…On the other hand, up to now, the mass transfer coefficient in CFBs are still mainly estimated on the basis of semi-empirical equations from experimental data-fitting in the literature (Breault., 2006). These mass transfer data in CFBs have been obtained by using ozone decomposition, naphthalene adsorption process, solid sublimation or liquid evaporation (Scala., 2007; Contents lists available at ScienceDirect Ouyang et al, 1995). These lead to mass transfer coefficient data published in the literature diverge significantly, reaching several orders of magnitude (Breault., 2006).…”
Section: Introductionmentioning
confidence: 96%